Evaluation of in vivo antibacterial drug efficacy using Caenorhabditiselegans infected with carbapenem-resistant Klebsiella pneumoniae as a model host - Yao, Huijuan; Xu, Ajing; Liu, Jingxian; Wang, Fang; Yao, Huimin; Chen, Jihui (Frontiers in Pharmacology, 2022)
Objective: This study was developed to assess the in vivo antimicrobial activity of specific drugs using a model system consisting of Caenorhabditis elegans(C. elegans) infected with Carbapenem-resistant Klebsiella Pneumoniae (CRKP) in an effort to identify promising drugs for CRKP-infected patient treatment. Methods: A C. elegans-CRKP liquid assay platform was developed and used to conduct limited in vivo screening for antimicrobial agents with potential activity against CRKP. Time curves for 10 different concentrations of tested antimicrobial agents were tested in this model system at 0, 2, 6, 8, and 12 h after treatment. The protective effects of these different antimicrobial compounds were compared at different time points. Furthermore, ten CRKP strains samples were isolated from clinical specimens to demonstrate the applicability of the nematode model method, and two typical clinical cases are presented. Results: CRKP bacteria were sufficient to induce C. elegans death in a dose- and time-dependent fashion, while effective antimicrobial agents improved the survival of these nematodes in a dose-dependent manner. Notably, PB and TGC exhibited robust antibacterial protection within 12 h even at low tested concentrations, and clear efficacy remained evident for high doses of CAZ at this same time point as mediators of improved nematode survival. The results of C. elegans model method were well consistent with that using the K-B method in 10 CRKP strains samples, and two typical clinical cases showed applicability, reliability and efficacy of C. elegans model method. Conclusion: Overall, nematode models in drug sensitivity testing have shown advantages in clinical settings. Our results highlight the value of C. elegans model systems as tools for the simultaneous screening of different compounds for in vivo antibacterial efficacy and is deserved to further study.